Gold-catalyzed cyclization of nonterminal propargylic amides to substituted alkylideneoxazolines and -oxazines - Hashmi, A. Stephen K.; Schuster, Andreas M.; Schmuck, Martin; Rominger, Frank (European journal of organic chemistry, 2011)
The substrate scope of the gold-catalyzed cyclization of nonterminal propargylic amides to oxazolines and oxazines was investigated. Sixteen alkyl-substituted and 35 aryl-substited substrates were prepared by a very variable route from trimethylsilyl-(TMS-)protected, nonterminal propargylamines. Steric and electronic influences of the substituents on product selectivity were studied. A chloromethyl substituent on the alkyne shows an efficient 1,4-elimination to deliver vinyloxazoles. A second alkynyl group, tethered to the alkyl group at the alkyne, in some cases led to a gold catalysis/Alder-ene domino reaction. With Barluenga's reagent the iodoalkylideneoxazoline can be formed in excellent yield. In contrast to the palladium-catalyzed protocols, the gold-catalyzed conditions for the cyclization of nonterminal propargylic amides are much milder, thus, for example, no special precautions are needed to prevent isomerization of the oxazolines to the aromatic oxazoles.
Gesehen am 07.09.2022